Analisis Potensi Piping Bendungan Menggunakan Persamaan Empiris dan Metode Elemen Hingga 3 Dimensi - Minmahddun, Anafi (Unmuh Babel Press, 2023)
Seepage is an inevitable occurrence in embankment dams, but under certain conditions, it can lead to piping. Piping is the formation of cavities in the soil due to the transport of fine soil particles by seepage forces. This phenomenon is one of the serious issues that can affect the stability of the dam. This study aims to analyze the potential for piping in one of the dams located in West Java using finite element and empirical equation methods. The finite element method analysis was conducted to obtain the exit hydraulic gradient values in the dam to calculate the safety factor against piping hazards. Meanwhile, the empirical equation used the weight creep ratio (WCR) to assess the potential for piping. The potential for piping analysis was conducted under minimum, normal, and flood water level conditions. The results of the finite element analysis showed that the hydraulic gradient exit values ranged from 0.20 to 0.33, resulting in safety factors ranging from 4.58 to 8.25. The obtained safety factors still meet the minimum safety factor criteria required by SNI 8065:2016, which is 4. The potential for piping analysis using the empirical approach yielded WCR values under the minimum, normal, and flood water level conditions, which were 4.71, 3.36, and 3.30, respectively. The calculated WCR values are higher than the typical value for WCR in hard rock, which is 1.6. Based on these two analyses, it can be concluded that the dam is safe against piping hazards.